1999
DOI: 10.1017/s1355838299990830
|View full text |Cite
|
Sign up to set email alerts
|

A novel 5′ displacement spin-labeling technique for electron paramagnetic resonance spectroscopy of RNA

Abstract: An RNA spin-labeling technique was developed using the well-characterized interaction between the HIV Rev peptide and the Rev response element (RRE) RNA as a model system. Spin-labeled RNA molecules were prepared by incorporating guanosine monophosphorothioate (GMPS) at the 59 end using T7 RNA polymerase and then covalently attaching a thiol-specific nitroxide spin label. Three different constructs of the RRE RNA were made by strategically displacing the 59 end within the native three-dimensional structure. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Finally, in addition to halogenation of uridines and cytosines for X-ray crystallography, other modifications are commonly used in structural studies of nucleic acids: ribose modification for EPR spectroscopy (Macosko et al 1999), 29-fluoro-nucleotides (Kreutz et al 2005(Kreutz et al , 2006 or 5-fluoropyrimidines (Marshall and Smith 1977;Rastinejad et al 1995) for NMR spectroscopy, introduction of various fluorescent bases for fluorescence studies (Qin and Pyle 1999;Yamana et al 1999;Ben Gaied et al 2005), or, more recently, incorporation of selenium for crystal structure determination (Wilds et al 2002;Hobartner and Micura 2004). Our results highlight the importance of checking the possible influence on RNA folding of even subtle nucleic acids modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in addition to halogenation of uridines and cytosines for X-ray crystallography, other modifications are commonly used in structural studies of nucleic acids: ribose modification for EPR spectroscopy (Macosko et al 1999), 29-fluoro-nucleotides (Kreutz et al 2005(Kreutz et al , 2006 or 5-fluoropyrimidines (Marshall and Smith 1977;Rastinejad et al 1995) for NMR spectroscopy, introduction of various fluorescent bases for fluorescence studies (Qin and Pyle 1999;Yamana et al 1999;Ben Gaied et al 2005), or, more recently, incorporation of selenium for crystal structure determination (Wilds et al 2002;Hobartner and Micura 2004). Our results highlight the importance of checking the possible influence on RNA folding of even subtle nucleic acids modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al reported a method for attaching nitroxides to the 5′ terminus of RNAs synthesized by the T7 RNA polymerase (53). In this method, a modified nucleotide, guanosine 5′-O-(3-thiomonophosphate) (GMPS), is added to a mixture of unmodified nucleoside triphosphates.…”
Section: B Nitroxide Labeling Using Enzymatic Methodsmentioning
confidence: 99%
“…All reported cw-EPR distance measurements in nucleic acids are examples of statically disordered spins, with the dipolar interaction manifesting itself as an overall spectral broadening (24,53). To use cw-EPR to measure the dipolar interaction between sites A and B of a macromolecule, three spectra should ideally be measured.…”
Section: A Short-range Distances Measured Using Cw-eprmentioning
confidence: 99%
See 1 more Smart Citation
“…SDSL utilizes a site-specifically attached nitroxide moiety that contains a stable, unpaired electron, and obtains local structural information by analyzing the electron paramagnetic resonance (EPR) spectrum of the nitroxide [8]. It is capable of providing information on high molecular weight assemblies under physiological conditions using a small amount of sample (∼5 μl of 50 μM of sample per measurement), and has been utilized to monitor solution structure and conformational changes at specific sites of RNA molecules [9][10][11][12][13][14][15][16] and to measure distances between two labeled sites within RNAs [17][18][19][20].An important source of information in RNA SDSL is the spectral lineshape of a singly labeled nitroxide [7]. In the conventional X-band measurements, the observed lineshape changes…”
mentioning
confidence: 99%